2013
DOI: 10.18388/abp.2013_1988
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastases of the A549-derived lung adenocarcinoma tumors growing in nude mice. A multiple case study.

Abstract: Lung adenocarcinoma is a leading human malignancy with fatal prognosis. Ninety percent of the deaths, however, are caused by metastases. The model of subcutaneous tumor xenograft in nude mice was adopted to study the growth of control and photodynamically treated tumors derived from the human A549 lung adenocarcinoma cell line. As a side-result of the primary studies, observations on the metastasis of these tumors to the murine lungs were collected, and reported in the present paper. The metastasizing primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…As shown in supplemental Figure 2, two peaks at g = 2.004 and g = 1.941 in heart tissue, liver tissue from mouse, and isolated mitochondria from bovine heart were also observed in our experimental condition. Similar ESR signals have been reported in many tumor cells, such as human cervical carcinoma HeLa cells [36], lung adenocarcinoma A549 cells [37], and several gastric tumor cells (T2-4, N0-2, M0-1, and G1-G4 cells) [29]. Emanuel reported that a narrow ESR signal at g = 2.004 is due to radicals of SQ, which are primarily localized in the mitochondria, and the broader signal at g = 1.94 originates from the non-heme iron of mitochondria containing sulfur compounds in various types of cancer [38].…”
Section: X-irradiation Increases Esr Signal Intensity At G = 2004 Insupporting
confidence: 84%
“…As shown in supplemental Figure 2, two peaks at g = 2.004 and g = 1.941 in heart tissue, liver tissue from mouse, and isolated mitochondria from bovine heart were also observed in our experimental condition. Similar ESR signals have been reported in many tumor cells, such as human cervical carcinoma HeLa cells [36], lung adenocarcinoma A549 cells [37], and several gastric tumor cells (T2-4, N0-2, M0-1, and G1-G4 cells) [29]. Emanuel reported that a narrow ESR signal at g = 2.004 is due to radicals of SQ, which are primarily localized in the mitochondria, and the broader signal at g = 1.94 originates from the non-heme iron of mitochondria containing sulfur compounds in various types of cancer [38].…”
Section: X-irradiation Increases Esr Signal Intensity At G = 2004 Insupporting
confidence: 84%
“…Secondly, some studies have demonstrated that A549 cells with different metastatic potentials in vivo . The metastatic potential of A549 cells to the lungs were found approximately 7% 47 . Moreover, c-MET protein activation or not in A549 cells could contribute to different metastatic pattern among different organs.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples obtained during autopsy were fixed in 5% buffered formalin (pH 7.4), embedded in paraffin and histologically sectioned into 5 µm thick slices using a Shandon Finesse 325 Microtome from Thermo. Standard hematoxylin and eosin staining was performed as described elsewhere 46 . Images of tissue samples were obtained using a Nikon Eclipse Ti-U inverted optical microscope coupled with a colored camera under a Plan 4 × objective.…”
Section: Methodsmentioning
confidence: 99%